Democratic sovereignty : authority, legitimacy, and state in a globalizing age / Matthew S. Weinert. - Weinert, Matthew S., 1970- (University College London Press, 2007)
"Democratic Sovereignty argues that sovereignty, generally defined as supreme authority in political community, has a neglected democratic dimension that highlights the expansion of substantive individual rights and freedoms at home and abroad. This volume offers a historically based assessment of sovereignty that neither reifies the state nor argues sovereignty and the state are withering, eroding, or disintegrating under globalizing processes. Rather, the book maintains that sovereignty norms have continually changed throughout the history of the sovereign state."--Jacket.